Mosaic changes to the global transcriptome in response to inhibiting ribosome formation versus inhibition of ribosome function - Shamsuzzaman, Md; Rahman, Nusrat; Gregory, Brian; Bruno, Vincent M.; Lindahl, Lasse (My University, 2020)
Cell fate is susceptible to several internal and external stresses. Stress resulting from mutations in genes for ribosomal proteins and assembly factors leads to many congenital diseases, collectively called ribosomopathies. Even though such mutations all depress the cell’s protein synthesis capacity, they are manifested in many different phenotypes. This prompted us to use Saccharomyces cerevisiae to explore whether reducing the protein synthesis capacity by different mechanisms result in the same or different changes to the global transcriptome. We have compared the transcriptome after abolishing the assembly of new ribosomes and inhibiting the translocation of ribosomes on the mRNA. Our results show that these alternate obstructions generate different mosaics of expression for several classes of genes, including genes for ribosomal proteins, mitotic cell cycle, cell wall synthesis, and protein transport.